The Hasmoneans and their neighbors: new historical reconstructions from the Dead Sea Scrolls and classical sources - Atkinson, Kenneth (Jewish and Christian texts in contexts and related studies, 2018)
"In this book Kenneth Atkinson adds to his already impressive body of work on the Hasmoneans, proposing that the history and theological beliefs of Jews during the period of the Hasmonean state cannot be understood without a close investigation of the histories of the Ptolemaic and the Seleucid Empires, as well as the Roman Republic. By bringing together evidence from the Dead Sea Scrolls and classical sources, Atkinson offers a new reconstruction of this vital historical period, from the 2nd to the 1st centuries B.C.E., when the Hasmonean family changed the fates of their neighbors, the Roman Republic, the religion of Judaism, and created the foundation for the development of the nascent Christian faith. The book also contains many new reconstructions of events in classical history, including the most detailed examination of Pompey the Great's assassination in light of Jewish sources. This section on his death uncovers new information that explains the discrepancies in the classical accounts of this pivotal event that shaped Middle Eastern and Roman history, and which helped end the Republic"